In Search of Utopia: Sylvia Pankhurst, Ethel Mannin, Nancy Cunard, and International Socialist Woman Authors in Interwar Britain - Timlin, Carrie (University of the Witwatersrand, Johannesburg, 2024)
A revival of anti-communist discourse in scholarship and politics has reignited decades-long debates between those who associate communism with the atrocities of totalitarian systems, and those who seek to emphasise the work of Socialists who genuinely sought to create a world free from gender, class and racial discrimination. In literary studies this has manifested as renewed interested in the lives and work of utopian Socialist authors like Nancy Cunard, Ethel Mannin and Sylvia Pankhurst, which suggests a shift in scholarship towards those outside the literary canon. Pankhurst and Mannin drew on literary forms that spoke to the culture, history, and experiences of their readers: women and the working classes. An exploration of the complexity of Cunard’s journey from attempts to infiltrate elitist literary circles, to a poet whose work captured the hardships of racial inequality and war, challenges ideas about the politics of modernist experimentation, and the value placed on high art. Taken together, their fiction and non-fiction unsettles the boundaries between art and activism, high, middle and lowbrow art, and preconceived ideas about the canon in the study of literature. Bringing their fiction and non-fiction into conversation with their socio-political contexts, readerships, and the philosophies and utopian socialist doctrine that shaped them as author-activists opens new avenues of exploration into the interplay of politics and aesthetics. Blurring the line between public politics, fiction and non-fiction, Pankhurst, Mannin, and Cunard’s work was a crucial and effective part of their internationalism, socialist activism, and resistance to totalitarianism. In the tradition of the utopianism of the late 19th Century they adapted literary forms as vehicles for socialist philosophy and doctrine. In addition to their creative work, they used literary techniques to shape non-fiction like newspaper articles, pamphlets and other political texts. The diversity of experience that Pankhurst, Mannin and Cunard recorded in their fiction and non-fiction amounts to an archive of work that complicates reductionist post-Cold War debates about the theory and practice of communism.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in English Literature to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; International Socialism; Ethel Mannin; Sylvia Pankhurst; Nancy Cunard; Aesthetics; SDG-5: Gender equality